Горн римского времени из Картала (к истории городища в III в. н.э.) - Бруяко, И.В.; Дзиговский, А.Н. (Материалы по археологии Северного Причерноморья, 2015)
In 2007 during the excavation on site Kartal the ceramic furnace was found. There were broken vessels in the loading cavity. All of them belonged to the category of the grey fictile pottery. In vessels collection there are distinguished of two main types – closed and open forms. According to the types of pottery the forge belonged to the Carpic-Dacian people, who inhabited on the territory of roman fort outskirts in the second half of III – the beginning of IV centuries A.D. At that time the fort was already neglected.